Phenotypic and genotypic analysis of influenza viruses isolated from adult subjects during a phase II study of intravenous zanamivir in hospitalised subjects - Yates, Phillip J.; Raimonde, Dawn S.; Zhao, Henry H.; Man, Choy Y.; Steel, Helen M.; Mehta, Nalini; Peppercorn, Amanda F. (Antiviral research, 2016)
Intravenous zanamivir (IVZ) is a neuraminidase (NA) inhibitor (NAI) under investigation for the treatment of subjects hospitalised with influenza. The study included 130 symptomatic, hospitalised adults with influenza. Subjects received IVZ for 5–10 days. Viruses were cultured and analysed for susceptibility to zanamivir. Mean IC50s (n = 50) (±SD) for influenza A/H1N1pdm09, A/H3N2 and influenza B were 0.20 ± 0.06, 0.26 ± 0.07 and 1.61 ± 0.35 nM, respectively, and are comparable to data observed for sensitive isolates. A total of 185 NA and 180 haemagglutinin (HA) sequences were obtained from 123 subjects; the majority did not contain resistance substitutions. Four influenza A/H1N1pdm09 viruses from four subjects harboured NA resistance substitutions: three, Y155H, D199G and S247N, were present at Day 1 before IVZ exposure and the fourth, E119D/E, was detected at Post Treatment +5 Days but was not present at 5 other timepoints. Five subjects harboured virus with treatment-emergent NA substitutions not associated with resistance; N63D, V83A, W190C, M269K (A/H1N1pdm09) and R210K (A/H3N2). Viruses from fifteen subjects harboured HA resistance substitutions, (A/H1N1pdm09) one emerged during treatment: S162N (Day 5). Five viruses harboured treatment-emergent HA substitutions (A/H1N1pdm09) not associated with resistance: E81K, V108L, S164D, D168N and S185N. 10/92 subjects with A/H1N1pdm09 harboured a D222 HA substitution, which has been associated with increased virulence. The emergent substitutions are not associated with resistance but may have arisen due to selection pressure during IVZ treatment or by chance. In this study, there was evidence for resistance selection in a post treatment sample but the resistant variant did not persist in later visit samples. •Mean IC50s (n = 50) for were similar to those previously reported for sensitive viruses.•The majority of viruses did not contain resistance substitutions.•Three A/H1N1pdm09 viruses harboured NA resistance substitutions at Day 1.•One resistance substitution, E119D/E, emerged at Post Treatment +5 Days.•Five subjects had treatment-emergent NA substitutions not associated with resistance.